The Influence of Audio Visual Media on Student Learning Outcomes - Dwiriyanti, Fina; Chadidjah, Sitti; Fadlani Salam, Mochamad; Supala; Kurniasih, Imas (Yayasan Mentari Madani, 2023)
This research aims to determine the relationship between the influence of the use of audio visual media on PAI learning outcomes and students' character. Learning using audio visual media is learning where educators can more easily convey material that is difficult for students to understand, and can provide understanding, experience, train them to think, focus more on learning Islamic Religious Education and Character by referring to values and teachings. -Islamic teachings so that students have good behavior and get good grades in learning. Continuously develop learning media for themselves so that students do not get bored while learning. So learning using audio-visual media has the aim of helping and as a tool for transferring knowledge from educators to students who believe in Allah and carry out his commands in accordance with the values of Islamic teachings. This type of research is descriptive quantitative research and the research design is correlational. The research sample used a systematic sampling technique, namely using special criteria for a sample of 60 respondents. The data collection technique uses observation, questionnaires and documentation techniques, while the data analysis technique uses descriptive and inferential statistical techniques using SPSS version 24.0 software. (1) The results of this research indicate that the level of achievement of Audio Visual Media on Student Learning Outcomes in Islamic Religious Education and Character Education Subjects for Classes VIII J and VIII K at SMP Negeri 1 Banjaran has increased significantly. This is proven by the total score obtained of 0.992 or 99.2% of the set criteria. (2) PAI teachers at SMP Negeri 1 Banjaran often use audio visual media when providing Islamic Religious Education lesson material. (3) The use of audio-visual media on student learning outcomes in Islamic Religious Education and Character subjects for classes VIII J and VIII K at SMP Negeri 1 Banjaran has a positive effect. This is proven by the results of the Pearson correlation test calculation of 0.505 with a significance value of 0.000 < 0.05, which means the correlation between variable X (Audio Visual Media) and Variable Y (Student Learning Outcomes) with a moderate correlation value